Studi Literatur Analisis Pengaruh Sosial Media Influencer dalam Meningkatkan Minat Investasi Milenial - Rachma, Alivia Maulidha; Hakim, Luqman; Jun Surjanti (Universitas Pendidikan Ganesha, 2024)
In Welcoming the Golden Generation of Indonesia 2045, it can be started by preparing the millennial generation in Indonesia today because it is a potential and important subject of investment in accelerating the economic growth of Indonesia in the future. The importance of this encourages the government and various parties to support guiding the millennial generation to have positive habits such as investing and avoiding consumptive behavior. The research conducted was aimed at determining the influence of social media influencers on investment interest variables for the millennial generation and conducting further analysis. The type of research used is SLR (Systematic Literature Review), with the PRISMA protocol; researchers analyzed based on journal publications with a time span between 2020-2024. The results of the research that has been conducted using the SLR method show that there is a positive influence between social media influencer variables and investment interest in the millennial generation.